Quantification of Glecaprevir and Pibrentasvir with Deuterated Internal Standards in Spiked Human Plasma Samples by LC–ESI-MS/MS - Alladi, Sharmila (Asian Journal of Pharmaceutics (AJP), 2022)
A fixed oral dose combination of Glecaprevir and Pibrentasvir used for the treatment of patients with viral infections especially used as an NS5A inhibitor. Quantification of such drugs in human plasma somewhat help full. In this manuscript, the authors developed a simple, sensitive, and specific liquid chromatography – tandem mass spectrometry method was used for quantification of Glecaprevir and Pibrentasvir in human plasma using Glecaprevir-13C-d7 as internal standard. Agilent TC-C18, 4.6 × 75 mm, 3.5 μm, 80 Å column, 5 mM ammonium acetate: Acetonitrile (20: 80 v/v) mobile phase was used for chromatographic separation. MRM-positive mode was used to detect the Glecaprevir, Pibrentasvir, and Glecaprevir-13C-d7 at m/z 838.87/337.26, 557.51/210.40, and 846.91/337.26, respectively. Liquid-liquid extraction was employed in the extraction of analytes and internal standard from human plasma. This method is validated over a linear concentration range of 50.0–10,000.0 pg/mL for Glecaprevir and Pibrentasvir with a correlation coefficient (r) of ≥0.9997. Both drugs were stable in plasma samples. The validated method was successfully.